Evaluasi Pengukuran Tingkat Kapabilitas Proses Pengelolaan Layanan, Pengelolaan Aset, dan Pengelolaan Operasi Menggunakan Framework COBIT 5 (Studi Kasus: PT. Pertamina (Persero) RU VI Balongan) - Lucky Hidayat; Suprapto Suprapto; Admaja Dwi Herlambang (Fakultas Ilmu Komputer (FILKOM), Universitas Brawijaya, 2018)
Pertamina (Persero) RU VI Balongan focused on operational management which included service delivery and asset management. To maximized the capability, operational management in the company should be evaluated to saw the capability of process that supported the company's business activities. One of the framework that used to evaluate IT Governance is COBIT 5. Where this aimed to evaluated related process like APO09 for manage service agreement, BAI09 for manage asset, and DSS01 for manage operation. By Used COBIT 5 framework, company knew how far the base practice had done and also supported documents that already applied from each process. And company are knew the capability levels of each process. Supported by qualitative method, where this research used interview technique, triangulation and observation, it helped for validated data from evaluation process and determined of the capability level in each process could be accurated with the condition in the company. From the evaluation of assessment capability level from each process, it would created a recommendation and solution to made improvement to achieved the expected level.